2020
DOI: 10.3390/agronomy10121937
|View full text |Cite
|
Sign up to set email alerts
|

Biofertilizers Enhance Quality of Onion

Abstract: This investigation was conducted to determine the effect of organic fertilizers on the content of chlorophyll a, chlorophyll b, antioxidant activity, crude fibre, and zinc in two onion cultivars, Stuttgarter Riesen and Rote Laaer, during 2016, 2017, and 2018. In this research, the following treatments were used: B-Stimul (contains Azospirillum Tarrand et al., Azotobacter Beij., Bacillus Cohn, Chlorella vulgaris Beij., and Herbaspirillum Baldani et al.), EkoBooster 2 (contains biostimulators and mineral salts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The objective of biofortification is to find ways to produce edible plants fortified with micronutrients that are easily assimilable by humans [111,112]. Research has shown that some crucifers [113], potato cultivars [114], onion cultivars [115], maize [116], and vegetable greens [117,118] could be biofortified with Zn or Fe. Manure applications could thus contribute to biofortification.…”
Section: Biofortification Vs Contaminationmentioning
confidence: 99%
“…The objective of biofortification is to find ways to produce edible plants fortified with micronutrients that are easily assimilable by humans [111,112]. Research has shown that some crucifers [113], potato cultivars [114], onion cultivars [115], maize [116], and vegetable greens [117,118] could be biofortified with Zn or Fe. Manure applications could thus contribute to biofortification.…”
Section: Biofortification Vs Contaminationmentioning
confidence: 99%
“…Biofertilizers may play an essential role in enhancing crop productivity and maintaining soil fertility in the long term while reducing the environmental burden associated with fertilizer production and nutrients leaching into groundwater deposits [44]. In addition, the microorganisms usually included in the biofertilizers might interact with the plants and boost their immunity, growth, and development, which consequently increase crop production [45][46][47]. The inoculation of peanut plants with mycorrhiza in the current study significantly enhanced the total chlorophyll, dry weight, and crop growth rate of groundnut plants (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Wu et al (2005) cleared that biofertilizer improved the growth substances such as indole acetic acid, gibberellins, as well as cytokinin materials. Many workers stated the beneficial effect of biofertilizers on onion quality and quantity such as Shaheen et al (2007), Abou El-Salehein et al (2014), Kumar et al (2019) and Rafique et al (2019).In general, biofertilizers can be successfully applied to onion plants under conditions which are favorable for the effective action of a particular kind of fertilizer, but the expectations of their potential should be reasonable (Petrovic et al 2020).…”
Section: Introductionmentioning
confidence: 99%